Consolidation of human capital values through finishing school approach. - Abdul Ghani, Che An; Md. Sabran, Shattar (2007)
Much has been said about the quality of our local graduates which do not meet the criteria sought by employers. For a country that has set the year of 2020 to be in the league of advanced countries, Malaysia does not have plenty of time to be lackadaisical. The country needs to be in the forefront in various science and technology disciplines and in humanitarian causes. We want to produce a well-rounded citizens who are intelligent, positive, creative and sensitive. Universities being the grooming centres to achieve these expectations have now, an additional task to produce high quality graduates. The graduates must be excellent academically and must also possess excellent human values. As such the term human capital was emphasized by the Ministry of Higher Education to public universities in the country. This broad term encompasses skills such as communication, team work, life-long learning, leadership, professional ethics and values, critical thinking and entrepreneursip. Collectively, these skills are known as soft skills. Universiti Putra Malaysia has taken the first step to respond to the call by introducing the concept of Finishing School. This is a two-day program that incorporates the seven skills mentioned and was offered to students who are in the last month of their final semester. Numerous creative activities were carried out to stimulate students interest to open up and break their rigid personality. This is especially noticeable as the course was run in English. This paper will highlight the perspective of the facilitators who have observed the transformation of the participants from the beginning to the end of the ccwrse and the consolidation of the human capital values.